Cloning and Embryo Splitting in Mammalians: Brief History, Methods, and Achievements - Mohaddeseh Rahbaran; Ehsan Razeghian; Marwah Suliman Maashi; Abduladheem Turki Jalil; Gunawan Widjaja; Lakshmi Thangavelu; Mariya Yurievna Kuznetsova; Pourya Nasirmoghadas; Farid Heidari; Faroogh Marofi; Mostafa Jarahian (Hindawi Limited, 2021)
Embryo splitting is one of the newest developed methods in reproductive biotechnology. In this method, after splitting embryos in 2-, 4-, and even 8-cell stages, every single blastomere can be developed separately, but the embryos are genetically identical. Embryo splitting, as an approach in reproductive cloning, is extensively employed in reproductive medicine studies, such as investigating human diseases, treating sterility, embryo donation, and gene therapy. In the present study, cloning in mammalians and cloning approaches are briefly reviewed. In addition, embryo splitting and the methods commonly used in embryo splitting and recent achievements in this field, as well as the applications of embryo splitting into livestock species, primate animals, and humans, are outlined. Finally, a perspective of embryo splitting is provided as the conclusion.